Morphological description of sinhondrosis of the spine against the background of experimental hypotheriosis - Talibnazarova Dildora Dilshatovna (Peerian Journals Publishing, 2025)
This study investigates the morphological characteristics of synchondrosis of the spine under conditions of experimental hypotheriosis. Structural changes, cellular responses, and tissue alterations are analyzed using histological and imaging techniques. The findings provide insights into the pathological processes and potential clinical implications for spinerelated disorders in hypothermic conditions
Keywords: synchondrosis; spine; hypotheriosis